# x^{2}+2x−1=x^{2}−x+2

Ernstfalld 2021-01-02 Answered
${x}^{2}+2x-1={x}^{2}-x+2$
You can still ask an expert for help

Expert Community at Your Service

• Live experts 24/7
• Questions are typically answered in as fast as 30 minutes
• Personalized clear answers

Solve your problem for the price of one coffee

• Available 24/7
• Math expert for every subject
• Pay only if we can solve it

## Expert Answer

Delorenzoz
Answered 2021-01-03 Author has 91 answers
SInce ${x}^{2}+2x-1={x}^{2}-x+2$ has an ${x}^{2}$ on both terms, simplify the equation by subtracting ${x}^{2}$ on both sides:
${x}^{2}+2x-1={x}^{2}-x+2$
${x}^{2}+2x-1-{x}^{2}={x}^{2}-x+2-{x}^{2}$
2x-1=-x+2
Next, we need to move the variable terms to the same side. Since the right side has −x, add xx on both sides to move the variable terms to the left side:
2x-1+x=-x+2+x
3x-1=2
Now we need to move the constants to the right side. Since the left side has subtraction of 1, add 1 on both sides to move the constants to the right side:
3x−1+1=2+1
3x=3
The last step is to isolate the variable. Since xx is being multiplied by 3, divide both sides by 3 to isolate x:
$\frac{3x}{x}=\frac{3}{3}$
x=1
The solution of the equation is then x=1.
###### Not exactly what you’re looking for?

Expert Community at Your Service

• Live experts 24/7
• Questions are typically answered in as fast as 30 minutes
• Personalized clear answers

Solve your problem for the price of one coffee

• Available 24/7
• Math expert for every subject
• Pay only if we can solve it